SOCS1 Mimetic Peptide Suppresses Chronic Intraocular Inflammatory Disease (Uveitis). (15th September 2016) - He, Chang; Yu, Cheng-Rong; Mattapallil, Mary J.; Sun, Lin; Larkin III, Joseph; Egwuagu, Charles E.
Abstract : Uveitis is a potentially sight-threatening disease characterized by repeated cycles of remission and recurrent inflammation. The JAK/STAT pathway regulates the differentiation of pathogenic Th1 and Th17 cells that mediate uveitis. A SOCS1 mimetic peptide (SOCS1-KIR) that inhibits JAK2/STAT1 pathways has recently been shown to suppress experimental autoimmune uveitis (EAU). However, it is not clear whether SOCS1-KIR ameliorated uveitis by targeting JAK/STAT pathways of pathogenic lymphocytes or via inhibition of macrophages and antigen-presenting cells that also enter the retina during EAU. To further investigate mechanisms that mediate SOCS1-KIR effects and evaluate the efficacy of SOCS1-KIR as an investigational drug for chronic uveitis, we induced EAU in rats by adoptive transfer of uveitogenic T-cells and monitored disease progression and severity by slit-lamp microscopy, histology, and optical coherence tomography. Topical administration of SOCS1-KIR ameliorated acute and chronic posterior uveitis by inhibiting Th17 cells and the recruitment of inflammatory cells into retina while promoting expansion of IL-10-producing Tregs. We further show that SOCS1-KIR conferred protection of resident retinal cells that play critical role in vision from cytotoxic effects of inflammatory cytokines by downregulating proapoptotic genes. Thus, SOCS1-KIR suppresses uveitis and confers neuroprotective effects and might be exploited as a noninvasive treatment for chronic uveitis.